Should the BK polyomavirus cytopathic effect be best classified as atypical or benign in urine cytology specimens?. Issue 6 (29th February 2016) - Allison, Derek B.; Olson, Matthew T.; Lilo, Mohammed; Zhang, Mingjuan L.; Rosenthal, Dorothy L.; VandenBussche, Christopher J.
Abstract : BACKGROUND: According to The Paris System for Reporting Urinary Cytology (TPS), the category of atypical urothelial cells (AUC) should not be applied to specimens in which cellular changes can be entirely attributed to the polyoma (BK) virus cytopathic effect (CPE). Until recently, cases with BK CPE at The Johns Hopkins Hospital were categorized as atypical urothelial cells of uncertain significance (AUC‐US), which is equivalent to the TPS AUC category. This study was performed to determine how significantly the rate of AUC‐US specimens would decrease if specimens with only BK CPE were classified as benign. METHODS: Two reviewers and 1 adjudicator re‐evaluated urinary tract specimens to determine whether sufficient cytological atypia justified an AUC‐US diagnosis independent of the presence of BK CPE. For patients with surgical follow‐up, the rate of high‐grade urothelial carcinoma (HGUC) on tissue biopsy was tracked over a 5‐year period. RESULTS: The reclassification rate of AUC‐US cases with BK CPE as benign was 62.6%. The rate of subsequent HGUC was 6.0% for cases reclassified as benign and 10.0% for cases still classified as AUC‐US. These rates were not significantly elevated in comparison with control cohorts among all‐comers. However, for patients without a history of HGUC, the rate of HGUC on follow‐up was significantly elevated in comparison with the rate for a benign control cohort and was similar to the rate for the AUC‐US control cohort. CONCLUSIONS: Reclassification as benign would have decreased the rate of AUC‐US from 24.8% to 20.7% during the study year. However, the high rate of subsequent HGUC among nonsurveillance patients suggests that the reclassification of specimens with BK CPE in these patients may be inappropriate. Cancer Cytopathol 2016;124:436–42 . © 2016 American Cancer Society . Abstract : When urinary cytology cases with polyoma (BK) virus are reclassified from atypical to benign, the diagnostic rate for the atypical category is reduced from 24.8% to 20.7%. However, patients with new‐onset hematuria have a high rate of high‐grade urothelial carcinoma on follow‐up, and this calls into question whether the reclassification of specimens with such findings into the benign category is appropriate.